"You need to be an advocate for yourself": Factors associated with decision-making regarding influenza and pneumococcal vaccine use among US older adults from within a large metropolitan health system. Issue 1 (2nd January 2017) - Kaljee, Linda M.; Kilgore, Paul; Prentiss, Tyler; Lamerato, Lois; Moreno, Daniela; Arshad, Samia; Zervos, Marcus
ABSTRACT: In the United States, influenza and pneumonia account significantly to emergency room use and hospitalization of adults >65 y. The Centers for Disease Control and Prevention recommends use of the annual influenza vaccine and 2 pneumococcal vaccines for older adults to decrease risks of morbidity and mortality. However, actual vaccine up-take is estimated at 61.3% for pneumococcal vaccines and 65% for influenza vaccine in the 2013–2014 season. Vaccine up-take is affected by multiple socio-cultural and economic factors including general healthcare access and utilization, social networks and norms, communication with health providers and health information sources, as well as perceptions related to vaccines and targeted diseases. In this study, 8 focus group discussions (total N = 48) were conducted with adults 65+ years living in urban and suburban communities in the Detroit Metropolitan Area. The research objective was to increase understanding of barriers and facilitators to vaccine up-take in this age cohort within the context of general healthcare availability and accessibility, social networks, information sources, and personal perceptions of diseases and vaccines. The data suggest the need to integrate broader health care service experiences, concepts of knowledge of one's own well-being and vulnerabilities, and self-advocacy as factors associated with older adults' vaccine-use decisions. These data also support recognition of multiple levels of vaccine acceptance which can be disease specific. Implications include potential for increasing vaccine up-take through general improvement in health care delivery and services, as well as specific vaccine-focused patient and provider education programs.